Analisis Manajemen Risiko Terhadap UMKM Ayam Geprek Raos - Ferdian, Adam Devan; Nuryanti, Mulani; Rizqi, Rissalam Akmalu (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study examines the risk management practices implemented by the UMKM Ayam Geprek Raos in facing the dynamics and challenges within the fast-food industry. The research employs a qualitative analysis using a case study approach, aiming to explore how risk management is applied in the daily operations of the business. Data collection was conducted through in-depth interviews with the business owner and several employees, along with direct field observations. The findings of the study identify various risks faced by Ayam Geprek Raos, including operational risks related to the quality of raw materials and supplier dependence, financial risks such as fluctuating cash flow, and marketing risks associated with changing consumer preferences. The risk management strategies employed by the business involve proactive measures, such as regular risk assessments, supplier diversification, and flexible marketing strategies to address market shifts. The study concludes that although Ayam Geprek Raos has implemented some effective risk management techniques, further development of risk mitigation strategies could help the business improve its resilience and competitiveness in the market.